Targeting heart rate as a novel therapeutic approach in acute heart failure - Imamdin, Aqeela (Department of Medicine, 2019)
Background and hypothesis: Standard pharmacological treatment for heart failure improves cardiac remodelling and survival in the setting of chronic heart failure, but is suboptimal in cases of acute heart failure (AHF). Peripartum cardiomyopathy (PPCM), de-novo hypotension (often due to haemorrhagic shock), and Takotsubo cardiomyopathy (TC) are conditions which have acute onset of heart failure, and often present with high mortality rates. In patients treated for these pathologies, a variation in the heart rate is observed and could potentially be used as a target to improve the treatment of AHF. We therefore questioned whether the use of a sinoatrial node inhibitor (ivabradine) to modulate heart rate may improve outcomes in AHF. Objectives and methods: Our objectives were 3-fold: (1) to explore the effect of a standard treatment strategy on heart rate in a South African cohort of PPCM patients after 6 and 12 months follow-up. (2) To explore the effect of ivabradine, a sinoatrial node inhibitor in an established signal transducer and activator of transcription 3 (STAT3) knockout mouse model of PPCM (with 3 consecutive pregnancies). Mice were fed ivabradine for 30 days (10mg/kg/day in drinking water), following the 3rd weaning. Trans-thoracic echocardiograms (TTE) were done at the end of the 3rd weaning, and after 30 days of treatment with ivabradine. Hearts were harvested after the second TTE for histology staining and messenger ribonucleic acid (mRNA) quantitation of transcripts involved in heart failure. (3) To explore the role of the sinoatrial node inhibitor in an ex-vivo model of de-novo AHF due to hypotension, and a newly developed ex-vivo model of TC. In the AHF model, hearts were stabilised before administering Ivabradine (3μM) in a buffer containing high free fatty-acids at a low pressure (to mimic hypotension/ haemorrhage shock conditions). A pressure- sensing balloon in the left ventricle measured heart rate, diastolic and systolic pressure, left ventricular developed pressure, rate pressure products and functional recovery. In the TC model, hearts were stabilised, then given a buffer with high free fatty-acid content and 10 times a physiological dose of adrenaline to mimic the adrenergic response seen in TC. Thereafter, hearts were restored to stabilisation pressure and substrate for recovery. Results: (1) Clinical outcomes indicated that patients on maximum standard therapy improved symptomatically and on the New York Heart Association scale. However, heart rates of PPCM patients remained elevated after 6 months of treatment. (2) In PPCM mice, a treatment with ivabradine was associated with reduced fibrotic infiltration in cardiac tissue and with a decrease in levels of atrial natriuretic peptide and Fibronectin mRNAs. (3) Both hypotensive AHF and TC models showed a tendency toward better cardiac function with ivabradine at the end of the acute phases. This advantage was lost after withdrawal of ivabradine during recovery. Conclusion: In South African women with PPCM treated with standard therapy, heart rate remains elevated, therefore suggesting that these women may benefit from the use of ivabradine as an additional therapy, particularly in patients who may be intolerant to β-blockers. The long-term use of ivabradine in the setting of cardiac dysfunction appears to have beneficial effects on remodelling, as treatment with ivabradine in our mouse PPCM model showed reduced cardiac fibrosis. The ex-vivo models of hypotensive AHF and TC both showed benefit in reducing heart rate during the acute phases, and hold the potential of being an intervention therapy to improve the outcome in patients who are brought to hospital while still in the acute phase.